Trends in Antimicrobial Allergies in Patients Seen in Infectious Disease Consultation During Selected Periods 2007–2016: Increases in Multidrug-Intolerant Individuals but Relative Stability in Antimicrobial Allergy Prevalence. Issue 2 (27th March 2022) - Liu, Hans H.; Mutneja, Hemant; Buckley, Meghan; Cushinotto, Lisa
Abstract : Background: Antimicrobial allergies and adverse reactions limit patient treatment options. "Antibiotic allergy" labeling drives broader, more toxic, and/or parenteral therapy. Published allergy data may be decades old over which time antibiotic usage has changed with newer agents introduced and greater use of several older ones. Some patient allergy designations are inaccurate; many are not true hypersensitivity. Electronic health records (EHRs) promote collection of allergy information but could inflate numbers as data are repetitively elicited and recorded. Objectives: This study measured antimicrobial allergy prevalence in hospitalized adults and determined how EHR implementation affected data. Methods: Retrospective chart reviews were conducted on 750+ adults seen in community teaching hospital infectious diseases consultation during each of three 6-month periods in 2007–2008, 2011–2012, and 2015–2016. Dates correspond to pre-EHR, after nursing data entry started, and after physician order entry and full electronic recordkeeping. Total antibiotic and nonantibiotic allergies were compiled and factors in recording these tracked. Results: Penicillin (20.5%–22%), cephalosporin (8%–10.2%), sulfa (12%–14.1%), and fluoroquinolone (5.4%–8.9%) allergy frequencies were high. Antibiotic allergy rates were stable from 2007–2008 to 2015–2016 due to most repetitive listings being made "inactive." However, median total drug allergies rose from 0 to 1 per patient ( P < 0.01) and multiple drug intolerance (>3 unrelated drugs) increased. Conclusions: Overall allergy rates for several antimicrobials were high but stable over study period; nonantibiotic allergies rose. Multidisciplinary allergy documentation is crucial in accurate data collection. Antibiotic-allergic and multiple drug intolerant patients are a good focus for prospective allergy education and "delabeling" programs.